2023
DOI: 10.3934/math.2023408
|View full text |Cite
|
Sign up to set email alerts
|

Stability, bifurcation, and chaos control in a discrete predator-prey model with strong Allee effect

Abstract: <abstract><p>This work considers a discrete-time predator-prey system with a strong Allee effect. The existence and topological classification of the system's possible fixed points are investigated. Furthermore, the existence and direction of period-doubling and Neimark-Sacker bifurcations are explored at the interior fixed point using bifurcation theory and the center manifold theorem. A hybrid control method is used for controlling chaos and bifurcations. Some numerical examples are presented to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Improper management of bifurcations can lead to disturbances in population dynamics and the consequent destruction of ecosystems. For a detailed bifurcation analysis, we recommend that readers refer to [31,[33][34][35][36][37][38][39].…”
Section: Local Bifurcation Analysismentioning
confidence: 99%
“…Improper management of bifurcations can lead to disturbances in population dynamics and the consequent destruction of ecosystems. For a detailed bifurcation analysis, we recommend that readers refer to [31,[33][34][35][36][37][38][39].…”
Section: Local Bifurcation Analysismentioning
confidence: 99%
“…Other recent studies on the dynamics of such games have been recently reported in the literature [28][29][30][31][32]. Recent studies on the complicated dynamics of such games have been reported in literature [33][34][35][36][37][38][39][40]. In addition, the case of Cournot-Bertrand on where decision variables are quantity and price has been recently studied in [41].…”
Section: Introductionmentioning
confidence: 99%
“…Discrete-time models provide the most precise depiction of the dynamics shown by animals that participate in seasonal reproduction and have nonoverlapping generations. In addition, discrete models exhibit much more complicated dynamical patterns as compared to continuous-time models [1,2,5,14,19,29,30,44]. Thus, discrete-time models are more appealing than continuous ones.…”
Section: Introductionmentioning
confidence: 99%